Theoretical and Practical Aspects of Translation (Journal of Pedagogical Inventions and Practices, 2022)
The study of the proper principles of translation is known as translation theory. Translation theory recognizes that various languages encode information in different ways, but enables translators to identify suitable ways of retaining meaning while employing the most appropriate forms of each language, based on a firm basis of understanding of how languages work. Principles for translating figurative language, coping with lexical incompatibilities, rhetorical inquiries, the use of cohesion markers, and a variety of other topics are all covered in translation theory.